Community Treatment Order Outcomes in Quebec: A Unique Jurisdiction. (July 2020) - Frank, Daniel; Fan, E; Georghiou, Angelos; Verter, Vedat
Objective: We study compulsory community treatment orders (CTOs) for patients with severe and persistent mental illness (SPMI). Focusing on a unique jurisdiction in Canada that allows for long duration CTOs with strict enforcement procedures, our objectives are to determine whether extended duration CTOs are effective and to determine whether associated hospitalization costs are reduced. Method: A mirror image, naturalistic design was employed using patients as their own controls to enhance external validity. No inclusive or exclusive criteria were employed for the 367 SPMI clinic patients who were studied over a 5-year period. Detailed documentation of the dates of all CTOs, long-acting antipsychotic injections (LAIs), emergency visits, hospitalizations, duration of hospitalizations, crimes and/or police involvement were collected. To study the relation between CTO and injection adherence, we use a mixed-effect linear regression model. To study the effect of injection adherence and hospitalization, we use survival analysis via Kaplan–Meier and Cox survival models. Results: CTO and non-CTO patients did not differ with respect to demographics, but CTO patients were significantly more severely ill. Following a CTO, adherence to LAIs increased over time ( P < 0.001). The average time the patients spent in the community, that is, outside the hospital, was significantly longer under a CTO, and the duration of hospitalizations was decreased. Conclusions: LAI adherence and outpatient office visits were enhanced by extended duration CTOs, as was time out of the hospital. The shorter duration of hospital stays implies cost savings. These must be weighed against their undesirable coercive nature.